Flow topology around low reynolds number eppler airfoils with vortex shedding - Che Ibrahim, Che Intan Hartini; Abdullah, Aslam; Razali, Mohd. Azahari (Asian Research Publishing Network (ARPN), 2022)
The flow topology has been widely discussed over the years and serves as motivation for the process of vortex formation and the periodic behaviour of the reattachment profile research studies. This study takes three low Reynolds number Eppler airfoils into account. The computational fluid dynamics simulations carried out involve the air flow passing these models. The attention is given mainly on the separation bubble, vortex shedding and reattachment point. The corresponding effects on airfoils aerodynamic performance is observed. The method is validated against an established data to indicate that both simulations and analysis technique are reliable. The results are useful in micro aerial vehicles application where the airfoils are those of low Reynolds number.